Photomechanical photochromism in a cetyltrimethylammonium isopolytungstate. Issue 34 (23rd May 2018) - Colusso, Aaron V.; McDonagh, Andrew M.; Gentle, Angus; Cortie, Michael B.
Abstract : The photochromic properties of a hybrid compound comprised of the surfactant cation cetyltrimethylammonium [(C16 H33 )N(CH3 )3 ] + and the isopolytungstate anion [H2 W12 O40 ] 6− is investigated. Abstract : The photochromic properties of a hybrid compound comprised of the surfactant cation cetyltrimethylammonium [(C16 H33 )N(CH3 )3 ] + (CTA + ) and the isopolytungstate anion [H2 W12 O40 ] 6− is investigated. The compound, which has the nominal formula (CTA)7 [H2 W12 O40 ]Cl·2H2 O, changes from white to blue when exposed to UV radiation. The sample returns to the bleached state if stored in the dark-ambient. Application of XPS indicates that the coloring species are W V and W IV . The CTA + component is found by XPS and FTIR to undergo progressive and irreversible oxidation during this cycle. Examination of FTIR suggests that the changes occur at multiple sites across the amphiphile. Surprisingly, the photochromic cycle is correlated with changes in the X-ray diffraction pattern, indicating partially reversible changes in the ordering of the Keggin ions and their spacing. In particular, application of the UV radiation causes the progressive accumulation of strain in the [001] direction. This is due to permanent oxidative changes in the CTA + accumulating from cycle to cycle, resulting in an increase in interlamellar-distance due to less interdigitation of the chains. This provides a controllable photomechanical response.